Babies and Boomers: Intergenerational Democracy and the Political Epidemiology of COVID-19. Issue 2 (1st December 2020) - Rollo, Toby
Abstract: The response to the COVID-19 pandemic has revealed how public health decisions in mass liberal democracies always reflect a political trade-off between protecting privileged groups and leaving more marginalized groups precariously exposed. Examining the "political epidemiology" of COVID-19, I focus on the ways that the lives and well-being of children are sacrificed to secure adult interests. I argue that in our efforts to protect older adults we have endangered children and abandoned the future of today's youth. This, I conclude, is indicative of a liberal preoccupation with adults and adult forms of agency, a defect that can only be adequately challenged by working toward more robust forms of democratic inclusion that include children and youth.